2020
DOI: 10.1080/19768354.2020.1765019
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of chrysin in diabetic neuropathy and formalin-induced pain models

Abstract: Chrysin, a natural flavonoid, is the main ingredient of many medicinal plants, which shows potent pharmacological properties. In the present study, the antinociceptive effects of chrysin were examined in ICR mice. Chrysin orally administered at the doses of from 10 to 100 mg/kg exerted the reductions of formalin-induced pain behaviors observed during the second phase in the formalin test in a dose-dependent manner. In addition, the antinociceptive effect of chrysin was further characterized in streptozotocin-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The von-Frey test was used to assess the pain threshold of mice. According to our previous procedures [ 52 ], mice were allowed to adapt to the test environment for 30 min by being placed in a transparent glass cell with a metal mesh floor. The von-Frey filament (North Coast Medical, Inc., Gilroy, CA, USA) was then applied to the plantar surface using the up and down paradigm [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The von-Frey test was used to assess the pain threshold of mice. According to our previous procedures [ 52 ], mice were allowed to adapt to the test environment for 30 min by being placed in a transparent glass cell with a metal mesh floor. The von-Frey filament (North Coast Medical, Inc., Gilroy, CA, USA) was then applied to the plantar surface using the up and down paradigm [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…RAW 264.7 cells (1 × 10 6 cells/well, in a 24-well plate) were pretreated with ME or PC for 1 h and stimulated with LPS (1 µg/mL) for 24 h. Then, the cells were harvested. According to our previous procedure [ 52 ], proteins were extracted using the lysis buffer and quantified with the Bradford method (Bio-Rad Laboratories, Hercules, CA, USA). The samples were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), then transferred to polyvinylidene fluoride (PVDF) membranes (Millipore, Bedford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The free radical scavenging capacity of chrysin can be attributed to the absence of oxygenation in their B and C-rings as in the carbonyl group on C-4. 11 It has been indicated that chrysin may activate antioxidant enzymes, increase mitochondrial permeability, regulate glutathione levels and restore mitochondrial dysfunction in diabetes mellitus, alleviating the complications of diabetes mellitus including neuropathy, retinopathy, and cardiomyopathy.- 11,12 Furthermore, recent studies showed that chrysin also exhibited osteogenic potential. Zeng et al found that chrysin treatment promoted the expression of osteogenesis genes as well as the formation of mineralized nodules in preosteoblast MC3T3-E1 cells via activation of ERK/ MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The nociceptive response was identified by counting the number of flinches of the injected paw. The number of flinches was counted for the periods of 0–5 min (neurogenic phase) and 10–60 min (Inflammatory phase) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%